The Danish Agricultural Revolution in an Energy Perspective: A Case of Development with Few Domestic Energy Sources - Sofia Teives Henriques; Paul Sharp (European Historical Economics Society (EHES), 2014)
Is a lack of domestic energy resources necessarily a limiting factor to growth, as suggested for example by the work of Robert C. Allen? We examine the case of Denmark - a country which historically had next to no domestic energy resources - for which we present new historical energy accounts for the years 1800-1913. Focusing on the period of the first Industrial Revolution, we demonstrate that Denmark's take off at the end of the nineteenth century was in fact relatively energy dependent. We relate this to her well-known agricultural transformation and development through the dairy industry. The Danish cooperative creameries, which spread throughout the country over the last two decades of the nineteenth century, were dependent on coal – a point which has not been stressed before in the literature. Denmark had next to no domestic coal deposits, but we demonstrate that her geography allowed cheap availability throughout the country through imports. Thus, Denmark might be seen as the exception that proves the rule: although modern energy forms are important for growth, domestic energy resources are not necessary, as long as it is possible to import them cheaply from elsewhere.
Keywords: N5; Q4; 330; Coal; dairying; Denmark; energy transition